Development and Application of a Triplex TaqMan Quantitative Real-Time PCR Assay for Simultaneous Detection of Feline Calicivirus, Feline Parvovirus, and Feline Herpesvirus 1 - Cao, Nan; Tang, Zhihui; Zhang, Xiyu; Li, Wanyan; Li, Bingxin; Tian, Yunbo; Xu, Danning (Frontiers in Veterinary Science, 2022)
As companion animals, felines play an important role in human's family life, and their healthcare has attracted great attention. Viruses such as feline calicivirus (FCV), feline herpesvirus 1 (FHV-1), and feline parvovirus virus (FPV) are the most common pathogens that cause severe infectious disease in baby cats. Thus, preclinical detection and intervention of these three viruses is an effective means to prevent diseases and minimize their danger condition. In this study, a triplex TaqMan quantitative real-time polymerase chain reaction (qRT-PCR) assay was developed to detect these three viruses simultaneously. The detection limit of FPV, FCV, and FHV-1 was 5 × 101 copies/assay, which exhibited higher sensitivity (about 10- to100-fold) than conventional PCR. The coefficients of variation (CVs) of the intra-assay variability were lower than 1.86%, and that of inter-assay variability were lower than 3.19%, indicating the excellent repeatability and reproducibility of the triplex assay. Additionally, the assay showed good specificity. Finally, samples from 48 cats were analyzed using the established assay and commercial kits. As a result, the total positive rates for these viruses were 70.83 or 62.5%, respectively, which demonstrated that the developed qRT-PCR assay was more accurate than the commercial kits and could be used in clinical diagnosis.